O mal-estar docente no contexto escolar a partir das percepções dos professores - Sanches, Ana Paula Rodrigues (2015)
The presented research would like to understand the process of ill be teaching in the school context from the teacher’s perceptions. For this work context, we make explicit some of the tensions of post-modernity and related issues to the teaching profession, seeking relationships with professional malaise. It is a qualitative research, from the inseparable link between objectivity and subjectivity, considering that the subject cannot be quantified in their feelings and actions. For this research, we selected two primary state education schools in Sorocaba. They hold opposing positions, in other words satisfactory or unsatisfactory results, in the education human development index of São Paulo State Education (IDESP) 2014. Using fifteen semi-structured questionnaires and interviews, we have checked and organized some possible indicators of ill-being between the employees in the school context, composing a general overview of the subject. From the categorization and analysis, a data triangulation, between them and the specific literature, we realized explicit perceptions of teachers about the ill-being feature in the school context and their possible implications for the current demands, class organization and working conditions. Some issues related to the ill-be can stand out, such as the lack of motivation and student’s indiscipline, school violence, long working hours and the pressure caused by external evaluations. About experiences on uncomfortable situations, the teaches emphasize the abuse of students with the professionals and also point the class attribution in the beginning of the school year and school administration impositions as main cause of this malaise. Thus, according the categories: the teacher malaise in the classroom and the teacher discomfort with working conditions and school training, we underline these teacher’s feelings in the teaching and learning process management, the way how it reach them in their school attribution and their prospects facing the problem the continuing education at school.